Learning from failure: cross-border confiscation in the EU. Issue 3 (2nd July 2019) - Pavlidis, Georgios
Abstract : Purpose: The purpose of this paper is to critically examine the strengths and weaknesses of a new European Union (EU) initiative attempting an interesting paradigm shift in the field of cross-border asset freezing and confiscation. The entry into force of the Lisbon Treaty and lessons learned from the manifest failure of past EU initiatives (Framework Decisions 2003/577/JHA and 2006/783/JHA) have allowed for such a paradigm shift for the strengthening of mutual recognition of freezing and confiscation orders in the EU. Design/methodology/approach: This paper draws on reports, legal scholarship and other open source data to examine a legislative innovation for the mutual recognition of freezing and confiscation orders in the EU. Findings: The EU legislative initiative that will be examined is innovative in nature and goes beyond international norms on cross-border asset freezing and confiscation. The new initiative needs to be integrated into the broader EU framework that targets criminal proceeds, and at the same time, to be anchored to respect for human rights. Originality/value: This study examines the strengths and weaknesses of an important new EU initiative, its compatibility with human rights standards and its relationship to international standards of cross-border asset freezing and confiscation.